2021
DOI: 10.1002/advs.202100995
|View full text |Cite
|
Sign up to set email alerts
|

The Green Lean Amine Machine: Harvesting Electric Power While Capturing Carbon Dioxide from Breath

Abstract: As wearable technologies redefine the way people exchange information, receive entertainment, and monitor health, the development of sustainable power sources that capture energy from the user's everyday activities garners increasing interest. Electric fishes, such as the electric eel and the torpedo ray, provide inspiration for such a power source with their ability to generate massive discharges of electricity solely from the metabolic processes within their bodies. Inspired by their example, the device pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(26 citation statements)
references
References 67 publications
2
24
0
Order By: Relevance
“…We also expected relatively low power output when using MEA and DEA, the solvents that form stable carbamate species, based on the analysis done in previous work that demonstrated that the carbamate formed by MEA had a much lower permeability than bicarbonate across the anion-exchange membrane. 38 We observed that DEA exhibited the highest viscosity and ammonia exhibited the lowest viscosity of the solvents tested, which aligns with DEA producing the lowest short circuit current and ammonia producing the highest short circuit current.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…We also expected relatively low power output when using MEA and DEA, the solvents that form stable carbamate species, based on the analysis done in previous work that demonstrated that the carbamate formed by MEA had a much lower permeability than bicarbonate across the anion-exchange membrane. 38 We observed that DEA exhibited the highest viscosity and ammonia exhibited the lowest viscosity of the solvents tested, which aligns with DEA producing the lowest short circuit current and ammonia producing the highest short circuit current.…”
Section: Resultssupporting
confidence: 74%
“…For example, in previous work, we captured approximately 0.6 mol of CO 2 per mol of MEA. 38 Nonetheless, we expected that these reactions reflected the general relationship of these CC solvents, and, because of the logarithmic relationship between salinity gradient and electric potential ( Supporting Information , Equations S1–S4 ), we considered this approximation to be sufficient for the comparison of the different CC solvents. We generated the rich solution for each CC solution by dispersing CO 2 into the solution until the pH stabilized ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations